Frailty Index Is a Significant Predictor of Complications and Mortality After Surgery for Adult Spinal Deformity. Issue 23 (1st December 2016) - Leven, Dante M.; Lee, Nathan J.; Kothari, Parth; Steinberger, Jeremy; Guzman, Javier; Skovrlj, Branko; Shin, John I.; Caridi, John M.; Cho, Samuel K.
Abstract : Study Design: Retrospective study of prospectively collected data. Objective: To determine if the modified Frailty Index (mFI) could be used to predict postoperative complications in patients undergoing surgery for adult spinal deformity (ASD). Summary of Background Data: Surgery for patients with ASD is associated with high complication rates and significant concerns present during risk stratification with older patients. The mFI is an evaluation tool to describe the frailness of an individual and how their preoperative status may impact postoperative survival and outcomes. Using a large nationwide database, we assessed the utility of this instrument in patients undergoing surgery for ASD. Methods: The American College of Surgeons National Surgical Quality Improvement Program is a large multicenter clinical registry that prospectively collects preoperative variables, patient demographics, operative factors, and 30-day postoperative morbidity and mortality outcomes from about 400 hospitals nationwide. Current Procedural Terminology codes were used to query the database for adults who underwent fusion for spinal deformity. The previously described mFI was calculated based on the number of positive factors and univariate and multivariate logistic regression analysis were used to analyze the risk factors associated with mortality. Results: Overall, 1001 patients were identified and the mean mFI score was 0.09 (range: 0–0.545). Increasing mFI score was associated with higher complication, reoperation, and mortality rates ( P < 0.05). mFI of 0.09 and 0.18 was an independent predictor of any complication, mortality, requiring a blood transfusion, pulmonary embolism/deep vein thrombosis, and reoperation (all P < 0.05). In comparison with age >60 years obesity class III, mFI was a superior predictor of several postoperative complications and reoperation. Conclusion: Frailty was an independent predictor of postoperative complications, mortality, and reoperation in patients undergoing surgery for ASD. Preoperative assessment of the mFI in this patient population can be utilized to improve current risk models. Level of Evidence: 3